Molecular Typing of RhD-Negative Blood Donors with C and/or E Antigen - Guzijan, Gordana (Scripta Medica, 2019)
Background: Most people are either RhD positive or RhD negative, but there is also a number of persons with D antigen variants. Aim: To prove, by using molecular diagnostic tests, whether the RHD gene and D antigen on the red cell membrane of the blood donors serologically typed as RhD-negative with RhD phenotype Ccddee and ccddEe, are so weak that they cannot be proven by serology techniques or the available anti-D test serums. Methods: Samples used are those of regular voluntary donors who were serotyped as RhD-negative, C and/or E positive. Samples were collected from voluntary donors at the Institute for Transfusion Medicine of the Republic of Srpska during the period from April 2016 to December 2018. Results: Among the serologically proven RhD-negative donors, 346 had C and/or E in their phenotype and those were subjected to molecular screening test. Conclusion: The first results of molecular typing match those published in literature, i.e. the RHD gene is present in some serologically RhD-negative forms, which was proven by molecular testing. Keywords: Rh system, D antigen, weak D, partial D